Problematising Home-based Care for Children with Cancer - Fletcher, Hannah Kate (2013)
Background and Literature Review This study explores issues around home-based care for children with cancer. Current policy tends to promote home-based care for children with cancer; this project seeks to interrogate that approach further and to explore the evidence base for this policy direction. The literature review is structured around key themes and demonstrates the gap in the evidence from health care professionals‘ perspectives and UK based research Methodology I adopt a qualitative approach to carry out in-depth and semi-structured interviews with a sample of 10 nursing staff that deliver care to children in the community, in hospital or between the two.